Affectivity, Somatic Symptoms and Psychological Pain as dimensions of Well-Being: A Pathways Model in Chilean university students - González-Arias, Mauricio (2023)
In order to evaluate the fit of a theoretical model to explain Mental Well-being from Positive and Negative Affect, Somatic Symptoms and Psychological Pain, 260 university students from Chile participated voluntarily, who answered the EBMWE, PANAS, SSS-8 and MBPPAS scales. The multivariate statistical technique of Path Analysis was used and the results indicated that Mental Well-Being is explained by direct relationships with Positive Affect, Negative Affect and Psychological Pain. Somatic Symptoms would have an indirect effect through Negative Affect and Psychological Pain. It is concluded that the variables of the model explain 72% of the variance of Mental Well-being.